Beyond regimes China and India compared - Duara, Prasenjit; Perry, Elizabeth J. (Cambridge, Massachusetts Published by the Harvard University Asia Center, 2018)
"Contemporary China and India have been powerfully shaped by trans- and subnational forces. This volume approaches China and India via a strategy of "convergent comparison," exploring local and global influences through a focus on labor relations; legal reform and rights protest; public goods provision; and transnational migration and investment"--Provided by publisher.
Part I. Labor relations: Variable forms of state capacity: state and labor in Shanghai and Mumbai in the 1950s / Mark W. Frazier -- Labor and state absenteeism: construction workers in India and China / T.G. Suresh -- Part II. Legal reform and rights protest: Contesting the right to law: courts and constitutionalism in India and China / Sanjay Ruparelia -- State-embedded villages: rural protests and rights awareness in India and China / Manjusha Nair -- Part III. Public goods provision: Parallel trajectories: the development of the welfare state in China and India / Nara Dillon -- Higher education reform in China and India: the role of the state / Devesh Kapur and Elizabeth J. Perry -- Part IV. Transnational migration and investment: Cosmopolitan capitalism: local state-society relations in China and India / Kellee S Tsai -- Foreign direct investment in China and India: history, economics, and politics / Min Ye.
Includes bibliographical references and index.
Keywords: Comparative government; Transnationalism; Industrial relations -- China; Industrial relations -- India; Civil rights -- China; Civil rights -- India; Comparative industrial relations; China -- Politics and government; India -- Politics and government; China -- Economic conditions; India -- Economic conditions